Memory truncated Kadanoff-Baym equations - Stahl, Christopher; Dasari, Nagamalleswara Rao; Li, Jiajun; Picano, Antonio; Werner, Philipp; Eckstein, Martin (Physical Review B, 2022)
The Keldysh formalism for nonequilibrium Green's functions is a powerful theoretical framework for the description of the electronic structure, spectroscopy, and dynamics of strongly correlated systems. However, the underlying Kadanoff-Baym equations (KBE) for the two-time Keldysh Green's functions involve a memory kernel, which results in a high computational cost for long simulation times tmax, with a cubic scaling of the computation time with tmax. Truncation of the memory kernel can reduce the computational cost to linear scaling with tmax, but the required memory times will depend on the model and the diagrammatic approximation to the self-energy. We explain how a truncation of the memory kernel can be incorporated into the time-propagation algorithm to solve the KBE, and investigate the systematic truncation of the memory kernel for the Hubbard model in different parameter regimes, and for different diagrammatic approximations. The truncation is easier to control within dynamical mean-field solutions, where it is applied to a momentum-independent self-energy. Here, simulation times up to two orders of magnitude longer are accessible both in the weak and strong coupling regime, allowing for a study of long-time phenomena such as the crossover between prethermalization and thermalization dynamics.
CRIS-Team Scopus Importer:2022-04-22

Photoinduced strange metal with electron and hole quasiparticles - Dasari, Nagamalleswara Rao; Li, Jiajun; Werner, Philipp; Eckstein, Martin (Physical Review B, 2021)
Photodoping of Mott insulators or correlated metals can create an unusual metallic state which simultaneously hosts holelike and electronlike particles. We study the dynamics of this state up to long times, as it passes its kinetic energy to the environment. When the system cools down, it crosses over from a bad metal into a resilient quasiparticle regime, in which quasiparticle bands are formed with separate Fermi levels for electrons and holes, but quasiparticles do not yet satisfy the Fermi-liquid paradigm. Subsequently, the transfer of energy to the environment slows down significantly, and the system does not reach the Fermi-liquid state even on the timescale of picoseconds. The transient photodoped strange metal exhibits unusual properties of relevance for ultrafast charge and heat transport: In particular, there can be an asymmetry in the properties of electrons and holes, and strong correlations between electrons and holes, as seen in the spectral properties.
CRIS-Team Scopus Importer:2021-06-11

Revealing Hund's multiplets in Mott insulators under strong electric fields - Dasari, Nagamalleswara Rao; Li, Jiajun; Werner, Philipp; Eckstein, Martin (Physical Review B, 2020)
We investigate the strong-field dynamics of a paramagnetic two-band Mott insulator using real-time dynamical mean-field theory. We demonstrate that strong electric fields can lead to a transient localization of electrons. This nonequilibrium quantum effect allows us to reveal specific signatures of local correlations in the time-resolved photoemission spectrum. In particular, we demonstrate that the localization can be strong enough to produce atomiclike spin multiplets determined by the Hund's coupling J, and thus provide a way of measuring J inside the solid. Our simulation also fully incorporates nonlinear field-induced tunneling processes, which would lead to a dielectric breakdown in the steady state limit. A careful analysis of these processes, however, shows that they remain weak enough and do not prevent the measurement of the transiently localized spectra.
CRIS-Team WoS Importer:2020-04-24

Ultrafast electric field controlled spin correlations in the Hubbard model - Dasari, Nagamalleswara Rao; Eckstein, Martin (Physical Review B, 2019)
Highly intense electric field pulses can move the electronic momentum occupation in correlated metals over large portions of the Brillouin zone, leading to phenomena such as dynamic Bloch oscillations. Using the nonequilibrium fluctuation-exchange approximation for the two-dimensional Hubbard model, we study how such nonthermal electron distributions drive collective spin and charge fluctuations. Suitable pulses can induce a highly anisotropic modification of the occupied momenta, and the corresponding spin dynamics results in a transient change from antiferromagnetic to anisotropic ferromagnetic correlations. To good approximation this behavior is understood in terms of an instantaneous response of the spin correlations to the single-particle properties.
CRIS-Team WoS Importer:2019-10-18

Ultrafast Spin Dynamics in Photodoped Spin-Orbit Mott Insulator Sr2IrO4 - Afanasiev, D.; Gatilova, A.; Groenendijk, D. J.; Ivanov, B. A.; Gibert, M.; Gariglio, S.; Mentink, J.; Li, Jiajun; Dasari, Nagamalleswara Rao; Eckstein, Martin; Rasing, Th.; Caviglia, A. D.; et al. (Physical Review X, 2019)
Ultrafast photodoping of the Mott insulators, possessing strong correlation between electronic and magnetic degrees of freedom, holds promise for launching an ultrafast dynamics of spins which cannot be described in terms of conventional models of ultrafast magnetism. Here we study the ultrafast laser-induced dynamics of the magnetic order in a novel spin-orbit Mott insulator Sr2IrO4 featuring an uncompensated pattern of antiferromagnetic spin ordering. Using the transient magneto-optical Kerr effect sensitive to the net magnetization, we reveal that photodoping by femtosecond laser pulses with photon energy above the Mott gap launches melting of the antiferromagnetic order seen as ultrafast demagnetization with a characteristic time of 300 fs followed by a sub-10-ps recovery. Nonequilibrium dynamical mean-field theory calculations based on the single-band Hubbard model confirm that ultrafast demagnetization is primarily governed by the laser-induced generation of electron-hole pairs, although the precise simulated time dependencies are rather different from the experimentally observed ones. To describe the experimental results, here we suggest a phenomenological model which is based on Onsager's formalism and accounts for the photogenerated electron-hole pairs using the concepts of holons and doublons.
CRIS-Team WoS Importer:2019-06-04